PEMBENTUKAN KATA PADA ALBUM LAGU LETHOLOGICA KARYA LETTO: KAJIAN MORFOLOGIS - Magfirotul Hamdiah; Jannatul Virdausiyah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to analyze word formation in Letto's Lethologica album from a morphological perspective. The research method used is descriptive qualitative. The research data are in the form of types, processes, and meanings of word formation in several song lyrics. While the source of research data is three song lyrics in Letto's Lethologica album. The data collection technique uses the listening method and the note-taking technique as a continuation. The results of this study indicate that there are 6 affixations, 5 reduplications, and 1 composition in the first song lyrics. 14 affixations, 3 reduplications, and 1 composition in the second song lyrics. 7 affixations, 2 reduplications, and 2 compositions in the third song lyrics. Thus, it can be concluded that the type of word formation that often appears is the affixation process.